2016
DOI: 10.3389/fphar.2016.00517
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Cocktail Phenotyping Study Protocol Using Physiological Based Pharmacokinetic Modeling and In silico Assessment of Metabolic Drug–Drug Interactions Involving Modafinil

Abstract: In vivo cocktail pathway phenotyping (ICPP) is routinely used to assess the metabolic drug–drug interaction (mDDI) potential of new drug candidates (NDC) during drug development. However, there are a number of potential limitations to this approach and the use of validated drug cocktails and study protocols is essential. Typically ICPP mDDI studies assess only the impact of interactions following multiple postulated perpetrator doses and hence the emphasis in terms of validation of these studies has been ensur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Changes in AUC and C max are shown in Figures 1 and 2, respectively. Consistent with reported simulations [2], analysis of pre-dose samples on Day 2 and Day 8 demonstrated that in all cases residual baseline probe concentrations were below the assay lower limit of detection, thus supporting complete clearance of the prior probe doses on Days 0 and 2, respectively.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Changes in AUC and C max are shown in Figures 1 and 2, respectively. Consistent with reported simulations [2], analysis of pre-dose samples on Day 2 and Day 8 demonstrated that in all cases residual baseline probe concentrations were below the assay lower limit of detection, thus supporting complete clearance of the prior probe doses on Days 0 and 2, respectively.…”
Section: Resultssupporting
confidence: 83%
“…In the current study, a model‐informed trial protocol was utilized to facilitate assessment of single dose and worst case steady state induction . As reported previously, pre‐specified PBPK modelling and simulation confirm that steady state exposure to modafinil is achieved within the 7‐day perpetrator dosing period recommended by the FDA for the assessment of induction and mechanism‐based inhibition mDDIs .…”
Section: Discussionsupporting
confidence: 59%
“…The models of the strong CYP3A4 inducer, rifampin, qualified by Simcyp . The modafinil PBPK model was qualified by comparing the predicted PK parameters after a single and multiple dose with the observed values . Furthermore, the observed AUC and C max ratios of palbociclib, triazolam, and midazolam in the presence and absence of modafinil are within 0.78‐ to 1.14‐fold of the observed values (Table S7).…”
Section: Resultsmentioning
confidence: 99%
“…The prediction of the effect of efavirenz (600 mg QD) was performed using the Simcyp v16 library file, implemented in Simcyp v14. The inducers were dosed orally for 12 days, and on day 7, a 200‐mg dose of abemaciclib was given concurrently with the dose of the inducer, except for the interaction with modafinil, where modafinil was dosed QD for 40 days, and abemaciclib was given on day 27 to reproduce dosing schedules from several published clinical trials …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation